2015
DOI: 10.1017/s0954102014000893
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric forcing of coastal polynyas in the south-western Weddell Sea

Abstract: The development of coastal polynyas, areas of enhanced heat flux and sea ice production strongly depend on atmospheric conditions. In Antarctica, measurements are scarce and models are essential for the investigation of polynyas. A robust quantification of polynya exchange processes in simulations relies on a realistic representation of atmospheric conditions in the forcing dataset. The sensitivity of simulated coastal polynyas in the south-western Weddell Sea to the atmospheric forcing is investigated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Between 20 and 50 cm, the uncertainty increases considerably. Therefore, we constrain our analysis accordingly as a thickness range of TIT ≤ 0.2 m is widely regarded as a threshold for polynya areas and for estimates of thermodynamic ice production in polynyas (Yu and Rothrock, 1996;Adams et al, 2013;Haid et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Between 20 and 50 cm, the uncertainty increases considerably. Therefore, we constrain our analysis accordingly as a thickness range of TIT ≤ 0.2 m is widely regarded as a threshold for polynya areas and for estimates of thermodynamic ice production in polynyas (Yu and Rothrock, 1996;Adams et al, 2013;Haid et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Haid et al (2015) found a large sensitivity of coastal polynya formation in the southwestern Weddell Sea to the atmospheric forcing for the sea ice-ocean model FESOM, using different coarse resolution global atmospheric analyses/reanalysis data and high-resolution COSMO model data. Major differences occur in mountainous areas where wind is strongly guided by surface topography.…”
Section: Katabatic Wind and Polynyasmentioning
confidence: 97%
“…In addition, a sea-ice/ocean model with enhanced horizontal resolution (3 km) was forced with the high-resolution data of the atmospheric model (Haid et al 2015). The mean wind field for the winter 2008 is presented in Fig.…”
Section: Katabatic Wind and Polynyasmentioning
confidence: 99%
“…The Finite-Element Sea ice-Ocean circulation Model (FE-SOM, Wang et al, 2014) is the first mature global multiresolution model designed to simulate the large-scale ocean. A number of FESOM-based studies related to the impact of local dynamics on the global ocean (see, e.g., Hellmer et al, 2012;Haid and Timmermann, 2013;Wekerle et al, 2013;Haid et al, 2015;Wang et al, 2016a;Sein et al, 2016;Wekerle et al, 2016) indicate that the multi-resolution approach advocated by FESOM is successful and allows one to explore the impact of local processes on the global ocean with moderate computational effort (see Sein et al, 2016). Other new global multi-resolution models are appearing (see Ringler et al, 2013), and new knowledge on unstructured-mesh modeling has accumulated (for a review, see Danilov, 2013).…”
Section: Introductionmentioning
confidence: 99%